К вопросу оценки эффективности использования информационных технологий обучения в процессе подготовки специалистов высшей школы - Караватская, Мария; Шабацкая, Светлана; Karavatska, Mariya; Shabatska, Svetlana (Східноєвропейський національний університет ім. Лесі Українки, 2013)
В работе изучены, обобщены и проанализированы данные, касающиеся проблемы оценки эффективности использования информационных технологий в процессе подготовки специалистов высшей школы. Описаны педагогические и дидактические условия, которые учитываются при разработке информационных систем, присущие для всей информационной сферы. Представлена информация о классификации информационных технологий, используемых при подготовке специалистов высшей школы. Особое внимание уделено описанию количественных и качественных показателей оценки эффективности, которые касаются использования информационных технологий в повышении уровня знаний студентов. In this work the data, corresponded to problem of estimation of effective application of information technology in the process of training of university students is investigated, generalized and analyzed. Pedagogical and didactic conditions, that are taken into account during the information system designing that are inherent for the whole information sphere are described. The classification of information technologies, used during the training of university students is presented. Particular attention is given to describe the qualitative and quantitative evaluation concerning the use of information technology in increasing students' knowledge.
To the Question of Estimation of the Use of Information Technologies of Studies in the Process of Preparation of Specialists of Higher School
Keywords: информационные технологии обучения; критерии эффективности; подготовка спе- циалистов; information technology of training; efficiency criteria; students training